HONOLULU - Møllegaard, Kirsten (Tidsskriftet Antropologi, 2003)
In the grand narrative of Honolulu as the gateway to the Land of Aloha, Honolulu metaphorically negotiates a position that mediates the contrasts between a typical socio-economic, urban reality and touristic myths of pastoral excoticism. Drawing on the critical works of postcolonial scholar Edward Said in conjunction with theories on semiotics and tourism, the article posits that two main factors contribute to reinforce and repeat the (neo)-colonial paradigm’s persistence in the grand narrative on Hawaii – namely aloha and nostalgia. Aloha functions conceptually as a unifying, pacifying force amongst the local population, while it defines the tourist gaze on Hawaii as a welcoming and politically uncomplicated holiday destination. Nostalgia, on the other hand, is the ideological interpretation of the past based on utopian desires in the present. Conjoined, aloha and nostalgia favor the tourist gaze and continue the hegemonic processes that colonize the minds of tourists and locals alike.